Alfonso Reyes: con la vida en guardia - Víctor Díaz Arciniega (Caravelle, 2010)
Alfonso Reyes went back to Mexico in 1939, on the eve of his fiftieth anniversary, and after having remained for the last 25 years of his life in France, Spain, Argentina and Brazil, occupying diplomatic charges and displaying a very rich literary activity. Then, as can be gathered from his works, his Diary and through his important public activities, he started his own personal task in order to make clear his definition and practice of humanism, considered as a civilizing function.